Hujjiyat Al-Qate' between the Possibility of Deterrence and its Impossibility (Asulogic - Jurisprudence study) - Hashem, Dr. Falah Abdul Hassan (Thi Qar Arts Journal, 2022)
The aim of the research is to clarify the meaning of the Hujjiyyat Al-qate', and whether they are subjective or not? Is it possible to deter them or not? If deterrence is not possible; What is the explanation for some of the resources that appear to be deprived of authenticity? It was well-known to say that the Hujjiyyat Al-qate' is subjective, and that it is not attained by the hand of the make to prove and negate, and they said that the disclosure of the qate' is a subjective matter to him, as the hujeyat is a subjective matter and the subjective does not explain. Thus, the Hujjiyyat Al-qate' becomes self-evident and necessary. However, some scholars, such as Sayyid Khomeini, have noticed that there is a confusion between Al-Kashfiyyah and Al-Hujjiyyah, and between Definiteness and Al-Kashfiyyah as well. This is because the subjective is in two sources, so it is either my isagogical subjective or my subjective from the section of the Book of Evidence.Based on the estimation of both meanings of the subjective, it cannot be applied to the revealing as well as to thehujjiyyah. Yes, with regard to the fact that the usology is not obtained by the hand of the make, this is correct, because it is one of the rulings decided by the mind - with the angel of necessity of obedience or repelling harm - and for that, it is dispensable from independent making.But her sufficiency in this is not because she is one of the requisites of the categorization and its subjectivity, but rather because the severing is one of its structural effects: the Kashafiyya, and in the opinion of the categorical, it does not lag behind; Because he sees its lump always exposed, so legislating it and making it is nonsense. After proving that the Hujjiyyah is not subjective, then as a proof, the authenticity can be taken away, and there is no mental caveat in that. Yes, there are some evidentiary caveats.We have mentioned a group of resources that may be said to support the issue of the separation between authenticity and categorization, and support the lack of authenticity from being subjective. There are, then, two opinions regarding the authoritativeness of exclusion and the possibility of deterrence: the opinion of the well-known who sees subjectivity, and another opinion adopted by Sayyid Khomeini and some of his students - such as Sayyid Mustafa Khomeini and al-Lankarani - who rejects the fact that the authoritative is subjective and sees the possibility of deconstruction between authenticity and exclusion. In the investigation: We favored the opinion of the well-known, but not with their statement that authenticity is subjective to deduction; That is why it is forbidden to disengage, but rather by a statement: that the Lord has the right of deterrence without a doubt, but the problem lies in how to deliver this deterrence to the taxpayer, so that its effect affects himself? Either he connects it to him by a factual ruling; And this necessitates from him the contradiction in the principles as we have shown, or he connects it to him by an apparent ruling, and the apparent ruling is subject to doubt, and in definiteness there is no doubt. In the end, and after this weighting, it was necessary to address what was said to be a deconstruction between authenticity and definiteness, and we have answered all the sources in which this disengagement was claimed, and we have made clear our opinion in it, in a way that does not deviate from the correct meaning of Hujjiyyah.